Mitigating climate change from early childhood education: an action research - Pérez Lisboa, Sandra (2021)
Climate change affects all countries, producing a negative impact on their economy, communities, natural environment and people. Education from childhood plays a fundamental role, so that children are involved in various habitual actions that allow them to act consciously and reflectively in a society of increasing scientific and technological changes. The objective of this action research was to develop knowledge, attitudes and values, to understand the effects of climate change on boys and girls of the Upper Middle level of a Kindergarten in the commune of San Felipe, Chile. Through participatory action research, the professional practice student carried out various learning experiences with 28 boys and girls, who learned mitigation and adaptation measures to climate change in the Aconcagua Valley. The results of the planned experiences allowed the development of attitudes and values in infants and the educational community. Likewise, open spaces for discussion around the responsibility of early childhood education centers, on climate change and how it affects the peace of communities. A través de la investigación participativa, la estudiante de práctica profesional realizó varias experiencias de aprendizaje con 28 niños y niñas, quienes aprendieron medidas de mitigación y adaptación al cambio climático en el Valle de Aconcagua. Los resultados de las experiencias planificadas permitirán el desarrollo de actitudes y valores en la infancia y la comunidad educativa. Asimismo, espacios abiertos de discusión en torno a la responsabilidad de los centros de educación infantil, sobre el cambio climático y cómo afecta la paz de las comunidades.